The Impact of Covid on the Income of Starful Farmers in Star Agro-Tourism Karangsari Village, Sukorejo District, Blitar City - Prayudhi, Luhur Aditya; Oryza Sativa, Rima Dewi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The impact of government policies is a decrease in PAD in the tourism sector. This policy makes it difficult for farmers to market their agricultural products. In addition to the Covid-19 pandemic, farmers feel that product prices have decreased due to a lack of consumer buying interest. and not worth their effort and operations. From there, it can be concluded that the formulation of the problem obtained is whether there was a difference in the income of star fruit before the covid-19 pandemic and during the Covid-19 pandemic and whether there was a difference in the feasibility of starfruit farming before and during the pandemic. The purpose of this study was to determine differences in starfruit income before and during, and to determine differences in the feasibility of starfruit business before and during the pandemic. year and during the covid 19 outbreak was Rp. 11,339,094/year. Analysis of the feasibility of starfruit farming in Karangsari Agrotourism, Blitar City, there is a difference where the RC Ratio is greater where before the covid 19 outbreak was 2.24 and during the covid 19 outbreak it was 1.79.